Proceedings of the 4th International Conference on the Durability of Concrete Structures 2014
DOI: 10.5703/1288284315431
|View full text |Cite
|
Sign up to set email alerts
|

Using Modified Mortar-Bar Test Method to Access the Effects of Deicers on Expansion of Mortars With and Without Reactive Aggregates

Abstract: The influence of deicing chemicals on alkali reactivity of aggregates is still an area of active research. The potential alkali reactivity of aggregates is often tested using the ASTM C1260 method. This research used the modified ASTM C1260 to test the potential alkali reactivity of aggregates. The modification included replacing the standard 1N sodium hydroxide (NaOH) used in ASTM C1260 with eutectic concentrations of the three common chloridebased deicing chemicals: sodium chloride (NaCl), magnesium chloride… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 4 publications
(2 reference statements)
0
1
0
Order By: Relevance
“…Accelerated mortar-bar testing (ASTM International 2013) was done to confirm the reactivity of the aggregates and determine which SCM would be a suitable option to mitigate ASR. As it is well published in the literature (Chiu & Olek 2014;Degirmenci et al 2011), mixes that expand more than 0.10 % at 16 days after casting are indicative of potentially deleterious expansion. Based on Figure 1, it is confirmed that aggregates are highly reactive as the mix containing Portland cement only had significantly higher expansion than the limit.…”
Section: Alkali-silica Reactionmentioning
confidence: 76%
“…Accelerated mortar-bar testing (ASTM International 2013) was done to confirm the reactivity of the aggregates and determine which SCM would be a suitable option to mitigate ASR. As it is well published in the literature (Chiu & Olek 2014;Degirmenci et al 2011), mixes that expand more than 0.10 % at 16 days after casting are indicative of potentially deleterious expansion. Based on Figure 1, it is confirmed that aggregates are highly reactive as the mix containing Portland cement only had significantly higher expansion than the limit.…”
Section: Alkali-silica Reactionmentioning
confidence: 76%